Analysis of Food Security and Livestock-Based Food Consumption Patterns among Poor Households in the Coastal Area of Demak Regency: Analisis Ketahanan Pangan dan Pola Konsumsi Pangan Ternak pada Rumah Tangga Miskin di Wilayah Pesisir Kabupaten Demak - Aryani, Yovita; Mukson, Mukson; Legowo, Anang Mohamad (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2025)
Demak Regency, despite being a food-producing area, faces potential food insecurity. This study analyzed household income, food and non-food expenditures, spending and consumption of livestock- based foods, and food security based on energy adequacy levels (EAL) and the share of food expenditures. The role of animal protein consumption was emphasized due to its importance in improving nutrition and food security among poor households. The research was conducted from October 2024 to March 2025 in Sayung (Tugu, Banjarsari) and Bonang (Purworejo, Morodemak) Subdistricts, purposively selected for their highest poverty levels. Using a survey of 104 households, data were collected through interviews, 2×24-hour food recall, and observation. The results showed that average income IDR 1,790,290.89/ month; food expenditure IDR 1,041,490.40; livestock-based food expenditure IDR 193,389.42; non- food expenditure IDR 744,884.16; livestock-based food consumption 48.10 g/capita/day; food insecurity dominated (73.08%), while 26.92% were food secure.